2010
DOI: 10.1111/j.1541-4337.2010.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Management of Listeria Monocytogenes in Ready‐to‐Eat Lettuce Salads

Abstract: Foodborne diseases constitute a major concern in societies, and their causes are aimed to be identified and minimized. Only in the last few years, this is encouraged by the application of risk assessment, management, and communication. This work presents a probabilistic quantitative microbiological risk assessment and management of Listeria monocytogenes in ready-to-eat lettuce salads in Spain. For risk assessment, a guideline provided by Codex Alimentarius was followed. Food chain was modeled from processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 53 publications
0
60
0
Order By: Relevance
“…These products are popular because they offer freshness, high nutritional value and convenience to consumers. Unfortunately, several outbreaks of food borne illness have been associated with fresh-cut lettuce in recent years (Carrasco et al, 2010;Delaquis et al, 2007;Luo et al, 2010;Harris et al 2003). Outbreaks caused by contamination with the verotoxigenic bacterium Escherichia coli O157:H7 are a significant concern given the severity of illness and potential long term sequela that may result from infection.…”
Section: Introductionmentioning
confidence: 99%
“…These products are popular because they offer freshness, high nutritional value and convenience to consumers. Unfortunately, several outbreaks of food borne illness have been associated with fresh-cut lettuce in recent years (Carrasco et al, 2010;Delaquis et al, 2007;Luo et al, 2010;Harris et al 2003). Outbreaks caused by contamination with the verotoxigenic bacterium Escherichia coli O157:H7 are a significant concern given the severity of illness and potential long term sequela that may result from infection.…”
Section: Introductionmentioning
confidence: 99%
“…in ready-to-eat food products, but most studies have been focused on bacterial pathogens such as Salmonella spp. (Sant'Ana et al, 2014;Franz et al, 2010), Listeria monocytogenes (Mataragas et al, 2010;Carrasco et al, 2010) and Escherichia coli 0157 (Strachan et al, 2006). Regarding HuNoV, a number of QMRA models have been developed to evaluate the risk of HuNoV in drinking water (Aström et al, 2007) and recreation water Soller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The risk output indicated that processed meats could be responsible for up to ~40% of cases of listeriosis in Australia, a level that could be in line with the available epidemiological data. Application of risk management measures for L. monocytogenes in ready-to-eat lettuce salads was made by Carrasco et al (2010). They showed that the most effective measures to reduce the risk of listeriosis were the use of specific mixture of gases in packages, the reduction of shelf-life to four days and the prevention of high-risk population from consuming ready-to-eat lettuce salads.…”
Section: Risk Assessment Needs and Questions For Risk Assessors mentioning
confidence: 99%